Green, pervasive, and cloud computing : 13th International Conference, GPC 2018, Hangzhou, China, May 11-13, 2018, Revised selected papers /: 13th International Conference, GPC 2018, Hangzhou, China, May 11-13, 2018, Revised selected papers. (2019) - Unknown
No abstract available